2010
DOI: 10.1177/1049732310361242
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Understanding of Sickness Absence Among Women Who Have Experienced Workplace Bullying

Abstract: Historically, we have assumed that workplaces, where employed individuals spend approximately one third of their days, provide safe and supportive environments and opportunities to enhance women's capacities. Unfortunately, workplace bullying and consequent sickness absence are prevalent and costly realities that significantly influence women's health. In this study, sickness absence among 18 Canadian women who were targets of workplace bullying was explored using a grounded theory secondary analysis. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
5
36
0
1
Order By: Relevance
“…Percentage of workdays absence cost associated with workplace mistreatment by occupation. Second, workplace mistreatment could increase sickness absence because of its negative impact on job satisfaction and commitment to work, and sickness absence may be used as a way to avoid or cope with the mistreatment [Quine, 1999;Cortina et al, 2001;Bowling and Beehr, 2006;O'Donnell et al, 2010;Nielsen and Einarsen, 2013]. As discussed earlier, the literature has shown that workplace mistreatment is associated with both physical and mental health problems [Björkqvist et al, 1994;Zapf et al, 1996;Kivimäki et al, 2003;Hallberg and Strandmark, 2006;Niedhammer et al, 2008;Lallukka et al, 2011].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Percentage of workdays absence cost associated with workplace mistreatment by occupation. Second, workplace mistreatment could increase sickness absence because of its negative impact on job satisfaction and commitment to work, and sickness absence may be used as a way to avoid or cope with the mistreatment [Quine, 1999;Cortina et al, 2001;Bowling and Beehr, 2006;O'Donnell et al, 2010;Nielsen and Einarsen, 2013]. As discussed earlier, the literature has shown that workplace mistreatment is associated with both physical and mental health problems [Björkqvist et al, 1994;Zapf et al, 1996;Kivimäki et al, 2003;Hallberg and Strandmark, 2006;Niedhammer et al, 2008;Lallukka et al, 2011].…”
Section: Discussionmentioning
confidence: 96%
“…Note that our $4.1 billion cost estimate did not include costs to employers in terms of reduced productivity, increased presenteeism, increased turnover (including costs associated with selecting, recruiting, and training), litigation/compensation, damaged corporate reputation, and decreased innovation [Namie, 2003;MacIntosh, 2005;Simons, 2008;Johnson, 2009;Hoel et al, 2010;O'Donnell et al, 2010;Beale and Hoel, 2011;Houshmand et al, 2012]. As Heames and Harvey [2006] indicated, by negatively affecting the work culture, damaging communication and relationship norms within the organization, and negatively affecting the ability of the organization to attract human capital, workplace mistreatment impacts not only employees, but also employers.…”
Section: Discussionmentioning
confidence: 99%
“…In these instances organisations need to address interpersonal issues if workers are to be able to successfully return to work. For example, studies on bullying in the workplace have found that changes in working conditions that remove or interrupt bullying are important indicators of returning to work (O'Donnell, MacIntosh, & Wuest, 2010). In O'Donnell et al's (2010, p.448) study of women affected by workplace bullying, they found that "adjusting was influenced by working conditions and organisational support."…”
Section: Relationship Conflict In the Workplacementioning
confidence: 94%
“…Aspects of reputation in the context of mobbing are abundantly analysed by different authors in different countries (D'Cruz & Rayner, 2013;Fox & Stallworth, 2010;Harvey et al, 2007;Hugh-Jones & Zultan, 2013;Katrinli, Atabay, Gunay, & Cangarli, 2010;Lutgen-Sandvik, 2008;Lutgen-Sandvik & Tracy, 2012;O'Donnell, MacIntosh, & Wuest, 2010). The damage of mobbing to health is discussed in scientific articles by the following authors: Duffy and Sperry (2007), Yildirim, Yildirim, and Timucin (2007), Testa (2013), Burgi (2014), Garot (2014), andSchindeler (2014).…”
Section: Theoretical Substantiationmentioning
confidence: 99%